Complete mitochondrial genome of the cockle Anadara antiquata (Linnaeus, 1758) - Liyun Pu; Hongtao Liu; Guofu Wang; Bingshun Li; Guangyuan Xia; Minghui Shen; Mingqiu Yang (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of Anadara antiquata was first determined. With a length of 45,454 bp, it consists of 29 tRNA, 2 rRNA, and 17 protein-coding genes (PCGs). The non-coding region was large and atypical around the genome with total 24,162 bp long. The nucleotide composition is significantly biased with AT contents of 62.2%. PCGs have five types of start codon, and terminate with a complete stop codon TAA or TAG. 19 microsatellites (SSRs) were identified in mitogenome sequences. Phylogenetic analysis demonstrated that A. antiquata was first clustered with Anadara vellicate, then together with Tegillarca granosa.